Rice Flowering Date Retrieval from Sentinel-2 and Planet Fusion Imagery - Sunil Kumar Jha; James Brinkhoff; Andrew J. Robson; Brian W. Dunn (Journal of the Indian Society of Remote Sensing, 2026)
Estimating the timing of rice flowering is useful for predicting maturity, which subsequently informs management decisions such as field drainage and harvest timing that optimize yield and quality. This study utilized satellite-based remote sensing to identify the highest measured vegetation index (VI) value, or peak of the season (PoS), which was correlated with observed rice flowering dates. Sentinel-2 (S2) and daily Planet Fusion (PF) data were used to derive four VIs and evaluate their effectiveness in determining rice flowering dates using an offset-adjusted peak-VI approach. Our methodology was tested in the major rice-growing regions of New South Wales, Australia, including commercial and experimental fields, multiple varieties, during the 2021–22, 2022–23, and 2023–24 seasons. Additionally, we assessed the extent to which variations in flowering dates induced by nitrogen content differences can be estimated. The results show that the chlorophyll index green (CIG) derived from PF provided a consistent relationship between PoS and observed flowering dates, with an offset of approximately 13 days and a root mean squared error (RMSE) of 6.56 and 7 days for the seasons 2021–22 (n = 114 sample sites) and 2022–23 (n = 134 sample sites), respectively. Furthermore, the study found that the method was able to describe the variation in flowering dates due to differences in nitrogen uptake at most sites, with $$\hbox {R}^2$$ values ranging from 0.09 to 0.97; higher explained variance was observed at sites where there was a wider range of flowering dates. The methodology facilitates the estimation of flowering dates and is scalable from pixel, to field, to regional level analysis.

Diagnosing scaling bottlenecks in 10 community conservation initiatives in southern and eastern Africa - Thomas Pienkowski; Matt Clark; Arundhati Jagadish; Aklei Albert; Mohanjeet Brar; Tarn Breedveld; Linda Chinangwa; Deepali Gohil; Deziderius Irumba; Ramzy Kanaan; Rose Peter Kicheleri; Phillip Kihumuro; et al. (Conservation Biology, 2026)
Scaling area‐based conservation, including initiatives led or comanaged by Indigenous Peoples and local communities, is a flagship goal of the Kunming‐Montreal Global Biodiversity Framework. Conservationists often aspire to scale initiatives, but this is rarely achieved in practice. Identifying and addressing factors that limit initiative adoption (i.e., bottlenecks) could improve scaling strategies. We used insightsfrom 84 expert surveys to identify potential risk factors and bottlenecks to scaling 10 community, area‐based initiatives in southern and eastern Africa. The number of reported potential risk factors and bottlenecks varied among initiatives. However, unfair benefit sharing, unequal decision‐making, inflexible rules, and top‐down leadership were frequently identified as bottlenecks. Although adopting initiatives had costs (e.g., increased local conflicts, reduced local access to natural resources and cropland), most experts believed these costs were offset by other benefits and thus did not constitute bottlenecks. Our results did not capture local perspectives, but they suggest scaling strategies that strengthen environmental governance may support more socially just and durable approaches to meeting area‐based conservation goals.

Contrasting Dynamic Behaviour of Five Lake-terminating Glaciers Draining the Vatnajökull Ice Cap and Links to Bedrock Topography - Nathaniel R. Baurley; Amelia Andrews; Benjamin Robson; Sherif Attia; Kirk Martinez; Jane K. Hart (Remote Sensing in Earth Systems Sciences, 2025)
Over recent years, the rapid growth and development of proglacial lakes at the margin of many of Iceland’s outlet glaciers has resulted in heightened rates of mass loss and terminus retreat, yet the key processes forcing their dynamic behaviour remain uncertain, particularly at those glaciers which are underlain by overdeepened bedrock troughs. As such, we utilised satellite remote sensing to investigate the recent dynamic changes at five lake-terminating glaciers draining the Vatnajökull ice cap. Specifically, we quantified variations in surface velocity between ~ 2008–2020, alongside datasets of frontal retreat, proglacial lake growth, bedrock topography and ice surface elevation change to better understand their recent dynamics and how this may evolve in future. We observed contrasting dynamic behaviour between the five study glaciers, with three displaying a heightened dynamic response (Breiðamerkurjökull, Fjallsjökull, Skaftafellsjökull), which was likely driven by retreat down a reverse-sloping bed into deeper water and the onset of dynamic thinning. Conversely, one glacier re-advanced (Kvíárjökull), whilst the other remained relatively stable (Svínafellsjökull), despite the presence of overdeepened bedrock troughs under both these glaciers, highlighting the complex nature of those processes that are driving the dynamic behaviour of lake-terminating glaciers in this region. These findings may be important in helping understand the processes driving the dynamics of other lake-terminating glaciers in Iceland so that their future patterns of retreat and mass loss can be more accurately quantified.

Microplastics and nanoplastics in haemodialysis waters: Emerging threats to be in our radar - Robson S. Passos; Andrew Davenport; Rosa Busquets; Clare Selden; Luiz B. Silva; J. Santos Baptista; Damià Barceló; Luiza C. Campos (Environmental Toxicology and Pharmacology, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

CropPol : A dynamic, open and global database on crop pollination - Alfonso Allen‐Perkins; Ainhoa Magrach; Matteo Dainese; Lucas A. Garibaldi; David Kleijn; Romina Rader; James R. Reilly; Rachael Winfree; Ola Lundin; Carley M. McGrady; Claire Brittain; David J. Biddinger; et al. (Ecology, 2022)
Seventy five percent of the world's food crops benefit from insect pollination. Hence, there has been increased interest in how global change drivers impact this critical ecosystem service. Because standardized data on crop pollination are rarely available, we are limited in our capacity to understand the variation in pollination benefits to crop yield, as well as to anticipate changes in this service, develop predictions, and inform management actions. Here, we present CropPol, a dynamic, open, and global database on crop pollination. It contains measurements recorded from 202 crop studies, covering 3,394 field observations, 2,552 yield measurements (i.e., berry mass, number of fruits, and fruit density [kg/ha], among others), and 47,752 insect records from 48 commercial crops distributed around the globe. CropPol comprises 32 of the 87 leading global crops and commodities that are pollinator dependent. Malus domestica is the most represented crop (32 studies), followed by Brassica napus (22 studies), Vaccinium corymbosum (13 studies), and Citrullus lanatus (12 studies). The most abundant pollinator guilds recorded are honey bees (34.22% counts), bumblebees (19.19%), flies other than Syrphidae and Bombyliidae (13.18%), other wild bees (13.13%), beetles (10.97%), Syrphidae (4.87%), and Bombyliidae (0.05%). Locations comprise 34 countries distributed among Europe (76 studies), North America (60), Latin America and the Caribbean (29), Asia (20), Oceania (10), and Africa (7). Sampling spans three decades and is concentrated on 2001–2005 (21 studies), 2006–2010 (40), 2011–2015 (88), and 2016–2020 (50). This is the most comprehensive open global data set on measurements of crop flower visitors, crop pollinators and pollination to date, and we encourage researchers to add more datasets to this database in the future. This data set is released for non‐commercial use only. Credits should be given to this paper (i.e., proper citation), and the products generated with this database should be shared under the same license terms (CC BY‐NC‐SA).

Accuracy of carrot yield forecasting using proximal hyperspectral and satellite multispectral data - Luz Angelica Suarez; Andrew Robson; John McPhee; Julie O’Halloran; Celia van Sprang (Precision Agriculture, 2020)
Proximal and remote sensors have proved their effectiveness for the estimation of several biophysical and biochemical variables, including yield, in many different crops. Evaluation of their accuracy in vegetable crops is limited. This study explored the accuracy of proximal hyperspectral and satellite multispectral sensors (Sentinel-2 and WorldView-3) for the prediction of carrot root yield across three growing regions featuring different cropping configurations, seasons and soil conditions. Above ground biomass (AGB), canopy reflectance measurements and corresponding yield measures were collected from 414 sample sites in 24 fields in Western Australia (WA), Queensland (Qld) and Tasmania (Tas), Australia. The optimal sensor (hyperspectral or multispectral) was identified by the highest overall coefficient of determination between yield and different vegetation indices (VIs) whilst linear and non-linear models were tested to determine the best VIs and the impact of the spatial resolution. The optimal regression fit per region was used to extrapolate the point source measurements to all pixels in each sampled crop to produce a forecasted yield map and estimate average carrot root yield (t/ha) at the crop level. The latter were compared to commercial carrot root yield (t/ha) obtained from the growers to determine the accuracy of prediction. The measured yield varied from 17 to 113 t/ha across all crops, with forecasts of average yield achieving overall accuracies (% error) of 9.2% in WA, 10.2% in Qld and 12.7% in Tas. VIs derived from hyperspectral sensors produced poorer yield correlation coefficients (R 2 < 0.1) than similar measures from the multispectral sensors (R 2 < 0.57, p < 0.05). Increasing the spatial resolution from 10 to 1.2 m improved the regression performance by 69%. It is impossible to non-destructively estimate the pre-harvest spatial yield variability of root vegetables such as carrots. Hence, this method of yield forecasting offers great benefit for managing harvest logistics and forward selling decisions.

A Blueprint for an Inclusive, Global Deep-Sea Ocean Decade Field Program - Kerry L. Howell; Ana Hilário; A. Louise Allcock; David M. Bailey; Maria Baker; Malcolm R. Clark; Ana Colaço; Jon Copley; Erik E. Cordes; Roberto Danovaro; Awantha Dissanayake; Elva Escobar; et al. (Frontiers in Marine Science, 2020)
The ocean plays a crucial role in the functioning of the Earth System and in the provision of vital goods and services. The United Nations (UN) declared 2021–2030 as the UN Decade of Ocean Science for Sustainable Development. The Roadmap for the Ocean Decade aims to achieve six critical societal outcomes (SOs) by 2030, through the pursuit of four objectives (Os). It specifically recognizes the scarcity of biological data for deep-sea biomes, and challenges the global scientific community to conduct research to advance understanding of deep-sea ecosystems to inform sustainable management. In this paper, we map four key scientific questions identified by the academic community to the Ocean Decade SOs: (i) What is the diversity of life in the deep ocean? (ii) How are populations and habitats connected? (iii) What is the role of living organisms in ecosystem function and service provision? and (iv) How do species, communities, and ecosystems respond to disturbance? We then consider the design of a global-scale program to address these questions by reviewing key drivers of ecological pattern and process. We recommend using the following criteria to stratify a global survey design: biogeographic region, depth, horizontal distance, substrate type, high and low climate hazard, fished/unfished, near/far from sources of pollution, licensed/protected from industry activities. We consider both spatial and temporal surveys, and emphasize new biological data collection that prioritizes southern and polar latitudes, deeper (> 2000 m) depths, and midwater environments. We provide guidance on observational, experimental, and monitoring needs for different benthic and pelagic ecosystems. We then review recent efforts to standardize biological data and specimen collection and archiving, making “sampling design to knowledge application” recommendations in the context of a new global program. We also review and comment on needs, and recommend actions, to develop capacity in deep-sea research; and the role of inclusivity - from accessing indigenous and local knowledge to the sharing of technologies - as part of such a global program. We discuss the concept of a new global deep-sea biological research program ‘ Challenger 150 ,’ highlighting what it could deliver for the Ocean Decade and UN Sustainable Development Goal 14.

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Recent multivariate changes in the North Atlantic climate system, with a focus on 2005–2016 - Jon Robson; Rowan T. Sutton; Alex Archibald; Fenwick Cooper; Matthew Christensen; Lesley J. Gray; N. Penny Holliday; Claire Macintosh; Malcolm McMillan; Ben Moat; Maria Russo; Rachel Tilling; et al. (International Journal of Climatology, 2018)
Major changes are occurring across the North Atlantic climate system, including in the atmosphere, ocean and cryosphere, and many observed changes are unprecedented in instrumental records. As the changes in the North Atlantic directly affect the climate and air quality of the surrounding continents, it is important to fully understand how and why the changes are taking place, not least to predict how the region will change in the future. To this end, this article characterizes the recent observed changes in the North Atlantic region, especially in the period 2005–2016, across many different aspects of the system including: atmospheric circulation; atmospheric composition; clouds and aerosols; ocean circulation and properties; and the cryosphere. Recent changes include: an increase in the speed of the North Atlantic jet stream in winter; a southward shift in the North Atlantic jet stream in summer, associated with a weakening summer North Atlantic Oscillation; increases in ozone and methane; increases in net absorbed radiation in the mid‐latitude western Atlantic, linked to an increase in the abundance of high level clouds and a reduction in low level clouds; cooling of sea surface temperatures in the North Atlantic subpolar gyre, concomitant with increases in the western subtropical gyre, and a decline in the Atlantic Ocean's overturning circulation; a decline in Atlantic sector Arctic sea ice and rapid melting of the Greenland Ice Sheet. There are many interactions between these changes, but these interactions are poorly understood. This article concludes by highlighting some of the key outstanding questions.

Mechanisms of decadal variability in the Labrador Sea and the wider North Atlantic in a high-resolution climate model - Pablo Ortega; Jon Robson; Rowan T. Sutton; Martin B. Andrews (Climate Dynamics, 2017)

Identifying avian sources of faecal contamination using sterol analysis - Megan L. Devane; David Wood; Andrew Chappell; Beth Robson; Jenny Webster-Brown; Brent J. Gilpin (Environmental Monitoring and Assessment, 2015)

Evolutionary transitions of complex labile traits: Silk weaving and arboreal nesting in Polyrhachis ants - Simon K. A. Robson; Rudy J. Kohout; Andrew T. Beckenbach; Corrie S. Moreau (Behavioral Ecology and Sociobiology, 2015)

Elevated plasma interleukin-6 levels in trained male triathletes following an acute period of intense interval training - Paula J. Robson-Ansley; Andrew Blannin; Michael Gleeson (European Journal of Applied Physiology, 2007)

Single Nucleotide +1 Frameshifts in an Apparently FunctionalMitochondrial Cytochrome b Gene in Ants of the Genus Polyrhachis - Andrew T. Beckenbach; Simon K.A. Robson; Ross H. Crozier (Journal of Molecular Evolution, 2005)

Conserved structure and function of the Arabidopsis flowering time gene CONSTANS in Brassica napus - Laurian S. Robert; Frances Robson; Andrew Sharpe; Derek Lydiate; George Coupland (Plant Molecular Biology, 1998)